2020
DOI: 10.1371/journal.pone.0239767
|View full text |Cite
|
Sign up to set email alerts
|

HIV-positive status disclosure and associated factors among children in public health facilities in Dire Dawa, Eastern Ethiopia: A cross-sectional study

Abstract: Introduction HIV status disclosure in children is one of acontroversial issue in current health. Over 44,000 children in Ethiopia were living with HIV in the year 2019 with a variable level of disclosure, which ranges from 16.3% to 49%. Therefore, this study aimed to assess HIV-positive status disclosure and associated factors among HIV-infected children. Methods A cross-sectional study was conducted in ten public health facilities providing pediatric antiretroviral therapy services. Systematic random sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…Among APHIV, prevalence of disclosure increased with age [ 12 , 14 , 15 ]. Other factors associated with disclosure include female gender, imminent onset of sexual debut, awareness of caregiver's HIV‐positive status and higher levels of caregiver education [ 12 , 16 , 17 , 18 ]. In contrast, reasons reported by caregivers for non‐disclosure include the child's young age, fear of disclosure's negative mental health consequences, risk of stigma if parents’ status is unmasked by child and unclear disclosure guidelines [ 9 , 10 , 14 , 15 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among APHIV, prevalence of disclosure increased with age [ 12 , 14 , 15 ]. Other factors associated with disclosure include female gender, imminent onset of sexual debut, awareness of caregiver's HIV‐positive status and higher levels of caregiver education [ 12 , 16 , 17 , 18 ]. In contrast, reasons reported by caregivers for non‐disclosure include the child's young age, fear of disclosure's negative mental health consequences, risk of stigma if parents’ status is unmasked by child and unclear disclosure guidelines [ 9 , 10 , 14 , 15 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-four studies [ 5 , 9 , 31 41 , 43 , 44 , 46 – 59 , 61 64 ] reported the prevalence rate of disclosure of HIV/AIDS status to infected children. Thirteen studies were from a low income country setting [ 5 , 32 – 34 , 38 40 , 46 , 49 , 51 , 59 , 62 , 63 ], fourteen studies were in a lower middle income country setting [ 31 , 35 37 , 41 , 44 , 47 , 48 , 52 , 53 , 55 , 56 , 58 , 61 ] and eight were from a upper-middle-income country [ 9 , 43 , 50 , 54 , 57 , 64 , 65 ]. The studies were published between 2008 and 2021, and the sample sizes ranged from 39 to 10,673.…”
Section: Resultsmentioning
confidence: 99%
“…It is consistent with a study done in Uganda which showed 56% in Jinja Hospital 6 and the study conducted in Dire Dawa showed 60.6%. 18 The possible explanation could be due to the same segment study population in which the study was conducted. However, the finding of this study was higher than the study conducted around Bale zone (28.5%), 17 Tanzania (32.6%), 3 Central Region of Ghana (23.3%), 19 and in Odi district (40%).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to a study done in East Gojjem, Gondar town, Bale, and Dire Dawa. 10 , 12 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%